2000
DOI: 10.1002/j.1552-4604.2000.tb05991.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 3‐Month Ingestion of Ginkgo biloba Extract on Pancreatic β‐Cell Function in Response to Glucose Loading in Normal Glucose Tolerant Individuals

Abstract: Ginkgo biloba extract is ingested on a chronic basis for enhancing mental focus and improving cognitive function in the elderly. This study was undertaken to determine the effect of Ginkgo biloba extract on glucose-stimulated pancreatic beta-cell function in normal glucose-tolerant individuals. Twenty individuals (14 females and 6 males, ages 21-57 years) underwent a 2-hour 75 g oral glucose tolerance test (OGTT) before and after ingestion of Ginkgo biloba extract (120 mg/day at bedtime) for 3 months. Ginkgo b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Quercetin, the main representative of the flavonol, found in high concentration in onions, apple, red wine, Ginkgo biloba, influences some carcinnogenosis markers [59][60][61][62][63][64][65][66]. Quercetin and its derivatives, as the principal polyphenol of Ginkgo biloba, might be partly responsible for its medicinal function of decrease in blood pressure [59]. Ulam raja, rich in proanthocyanidins, chlorogenic acids and quercetin and its derivatives, might also have these biological functions.…”
Section: Potential Beneficial Effects Of Consuming Ulam Rajamentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin, the main representative of the flavonol, found in high concentration in onions, apple, red wine, Ginkgo biloba, influences some carcinnogenosis markers [59][60][61][62][63][64][65][66]. Quercetin and its derivatives, as the principal polyphenol of Ginkgo biloba, might be partly responsible for its medicinal function of decrease in blood pressure [59]. Ulam raja, rich in proanthocyanidins, chlorogenic acids and quercetin and its derivatives, might also have these biological functions.…”
Section: Potential Beneficial Effects Of Consuming Ulam Rajamentioning
confidence: 99%
“…Chlorogenic, as a natural antioxidants, is able to chelate iron [56] and protect against oxidative stress [57] and DNA damage [58]. Quercetin, the main representative of the flavonol, found in high concentration in onions, apple, red wine, Ginkgo biloba, influences some carcinnogenosis markers [59][60][61][62][63][64][65][66]. Quercetin and its derivatives, as the principal polyphenol of Ginkgo biloba, might be partly responsible for its medicinal function of decrease in blood pressure [59].…”
Section: Potential Beneficial Effects Of Consuming Ulam Rajamentioning
confidence: 99%
“…Studies have suggested that GbE intake by type 2 diabetes mellitus (T2DM) patients reduces circulatory diseases and improves the glycemic profile (11,12). Reduced glycemia was also reported in streptozotocin-induced diabetic rats (13).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced glycemia was also reported in streptozotocin-induced diabetic rats (13). It has been suggested that these beneficial effects could result from a significant stimulation of pancreatic beta-cell function/insulin production (11) and from a significant decrease in glycated hemoglobin levels of T2DM patients (14). Despite the evidence for a positive effect of GbE on glycemic homeostasis, data in the literature are scarce about the action of GbE on obesity-related insulin intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…For over a decade, we have studied the effect of Ginkgo biloba extract on several parameters including pancreatic β-cell function and whole body insulin sensitivity in normal glucose tolerant individuals, those with impaired glucose tolerance and people suffering from type 2 diabetes mellitus (T2DM) [11]- [13]. During these studies the volunteers completed monthly questionnaires and were encouraged to provide other general comments about how they felt after ingesting the Ginkgo biloba extract.…”
Section: Introductionmentioning
confidence: 99%